AB0795 Cardiovascular Preventive Medication and Treatment Targets in Patients with Osteoarthritis: Results from the Must-Heart Study. (10th June 2014) - Rollefstad, S.; Eeg, I.K.; Haugen, I.K.; Østerås, N.; Kvien, T.K.; Semb, A.G.
Abstract : Background: Guidelines recommend cardiovascular (CV) preventive pharmacotherapy when the CV risk evaluated by SCORE is ≥5% (primary prevention), and after diagnosed CV disease (secondary prevention). Undertreatment and poor goal attainment of blood pressure (BP) and lipid goals in both primary and secondary prevention has been reported in the general population. 1, 2 Objectives: Our aim was to evaluate CV primary and secondary preventive treatment and attainment of recommended goals in patients with OA in the Musculoskeletal pain in Ullensaker STudy (MUST). Methods: The MUST is a population-based postal survey and a comprehensive clinical examination of persons with self-reported osteoathritis (OA) (MUST OA cohort) (n=630), of which 438 fulfilled the ACR criteria for OA. In the MUST-Heart study, usage of primary and secondary CV preventive medication as lipid lowering agents (LLA), anti-hypertensive medication (a-HT) and anti thrombotic medication (AT) (acetylsalicylic acid and dipyridamole) was recorded. Guideline recommended BP goal is ≤140/90 mmHg, and low density lipoprotein cholesterol (LDL-c) goals for primary/secondary prevention are ≤2.5/≤1.8 mmol/L, respectively. Attainments of BP and lipid targets for patients on the respective medications were evaluated. Results: Secondary or primary CV prevention was indicated in 72 and 26 patients, respectively. The female/male ratios 45/27 and 5/21 and the median (IQR) age was 68.5 (65.0, 75.8) years and 66.5 (65.0, 73.8) years. Total Cholesterol (TChol) was: 5.17 (1.25) (SD) mmol/L/5.97 (1.19) mmol/L, high density lipoprotein cholesterol (HDL-c): 1.49 (0.46) mmol/L/1.22 (0.29) mmol/L, LDL-c: 2.97 (1.06) mmol/L/3.82 (1.06) mmol/L, BP was 140.5 (18.7)/82.4 (8.3) mmHg/155.7 (14.5) mmHg/87.2/10.1 mmHg, for the secondary/primary prevention groups. Of the 72 patients with diagnosed CV disease, 38 (52.8%) were using LLA, 47 (65.3%) a-HT medication and 25 (34.7%) were on AT medication. Of the 125 patients (without CV disease) who had hypertension, 57 (45.6%) used a-HT medication. Of the 26 patients with a calculated CV risk by SCORE ≥5%, 2 (7.7%) used LLA. Of the patient who were using a-HT medication, BP goal attainment was 20/47 (42.6%) and 0/57 (0%) for patients in the secondary and primary prevention groups. Of all patients using LLA, patients with CV disease achieved goals for TChol were 12/38 (31.6%) and LDL-c: 9/38 (23.7%). Conclusions: There was a substantial underuse of cardio-protective drugs in persons with OA in the MUST-Heart study, which resulted in poor attainment of recommended BP and lipid targets. The goal achievement of BP and lipids in patients with OA is even lower than reported for the general population. References: Devroey D, Radermecker RP, Van der Schueren BJ, Torbeyns B, Jaken RJ. Prevalence of persistent lipid abnormalities in statin-treated patients: Belgian results of the Dyslipidaemia International Study (DYSIS). Int J Clin Pract 2013. Prugger C, Keil U, Wellmann J, De BD, De BG, Ambrosio GB et al. Blood pressure control and knowledge of target blood pressure in coronary patients across Europe: results from the EUROASPIRE III survey. J Hypertens 2011; 29(8):1641-1648. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5387